Workers' participation : a voice in decisions, 1981-85 - Monat, Jacques; Sarfati, Hedva (Geneva : International Labour Office, 1986)
This volume points to the growing body of evidence to support the view that considerable developments have been taking place in recent years in the field of workers' participation at the enterprise level. This round-up of selected articles drawn, in full or in part, from the ILO's quarterly Social and Labour Bulletin (subsequently referred to by the acronym SLB), illustrates how workplace participation has evolved over the past five years in different national settings.
Includes bibliographical footnotes and index.
hza 16/07/2018
Loans
Keywords: Management